Penatalaksanaan Psoriasis Terkini - M. Mimbar Topik; Nabila Tacha (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Psoriasis is a chronic skin inflammation with a strong genetic basis. In the skin of psoriasis patients, there are changes in the growth and differentiation of epidermal cells. The term psoriasis comes from the Greek 'psora' which means itching. Psoriasis is a chronic skin inflammation characterized by well-defined erythematous plaques, rough scales, layers and silvery white in color, especially on the elbows, knees, scalp, back, umbilicus and lumbar. Initially psoriasis was thought to be a disease of abnormal proliferation and differentiation of keratinocytes. Psoriasis precipitating factors can vary, including infection, topical irritant agents, and systemic steroids. Precipitating factors are usually involved in the initial manifestation of psoriasis or lead to an exacerbation of the disease. Psoriasis is currently known to have a close relationship with comorbidities such as psoriatic arthritis, obesity, cardiovascular disease, non-alcoholic liver disease, metabolic syndrome, and inflammatory bowel disease that can worsen quality of life and reduce patient life expectancy.